Marketing Information System for Maize Commodities in Soppeng Regency to Increase Agricultural Productivity and National Food Security - Asnia Minarti; Ismail Ismail; Nursakti Nursakti (Maneggio, 2024)
Maize in Soppeng Regency is a strategic commodity and has bright marketing prospects. Therefore, efforts to increase maize production need to receive great attention, because with sufficient availability, maize is one of the main food needs in the world after rice. It is expected that the community's need for maize can be met and the selling price remains stable. This research aims to increase the productivity of corn commodity marketing in Soppeng Regency based on the application of online marketing information systems, so that the market world can be wider and make it easier for farmers to sell their corn commodity products and become corn crop production centers, in order to increase the productivity of food crops, especially in Soppeng Regency. This study uses preliminary data on corn production from villages and sub-districts sourced from the Office of Food Crops, Horticulture, Plantations, and Food Security of Soppeng Regency which consists of 49 villages, 21 sub-districts and 8 sub-districts. The system development method uses the SDLC (System Development Life Cycle) system development technique, the application of this method starts from the field condition analysis stage, the system design stage, the system creation stage, the system testing stage, the system usage stage in the field. In addition, to meet the sustainability of the program, technical guidance on the use of the system will be provided to each user at the sub-district level. The results of this research are in the form of using an online-based corn commodity marketing information system